Evaluating the suitability of state‐based formal methods for industrial deployment. (13th September 2018) - Mashkoor, Atif; Kossak, Felix; Egyed, Alexander
Summary: After a number of success stories in safety‐critical domains, we are starting to witness applications of formal methods in contemporary systems and software engineering. However, one thing that is still missing is the evaluation criteria that help software practitioners choose the right formal method for the problem at hand. In this paper, we present the criteria for evaluating and comparing different formal methods. The criteria were chosen through a literature review, discussions with experts from academia and practitioners from industry, and decade‐long personal experience with the application of formal methods in industrial and academic projects. The criteria were then evaluated on several model‐oriented state‐based formal methods. Our research shows that besides technical grounds (eg, modeling capabilities and supported development phases), formal methods should also be evaluated from social and industrial perspectives. We also found out that it is not possible to generate a matrix that renders the selection of the right formal method an automatic process. However, we can generate several pointers, which make this selection process a lot less cumbersome.